2021
DOI: 10.33545/gynae.2021.v5.i4c.977
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive usage and preferences among young married women in Himachal Pradesh

Abstract: Background: In India, there has been a population explosion in the last century, the most common method of contraception in India is female sterilization. With the increasing literacy rate, there should have been a shift towards reversible methods of contraception among females. This paper describes the use and preferences of contraceptive methods among young married women in rural parts of Hamirpur district in Himachal Pradesh, India. Subjects and Methods: A hospital-based cross-sectional survey was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the post partum period, 70% women reported that they were sexually active within 6 months of child birth. 46% had resumed menstruation within 12 weeks, but the use of [13] contraception in this period was only 23%.…”
Section: Discussionmentioning
confidence: 98%
“…In the post partum period, 70% women reported that they were sexually active within 6 months of child birth. 46% had resumed menstruation within 12 weeks, but the use of [13] contraception in this period was only 23%.…”
Section: Discussionmentioning
confidence: 98%